FMCW Multipulse Radar System For Improved Vehicle Speed Detection Capabilities - Sania Uswah Nafisah; Ahmad Sugiana; Aloysius Adya Pramudita (eProceedings of Engineering, 2026)
Accidents on toll roads are often caused by vehicles exceeding the legal speed limit. To mitigate this, a reliable speed detection system is required—one that offers a wide detection range, high accuracy, and the flexibility to be integrated into a vehicle’s body. One promising solution is the use of Doppler radar based on the Frequency-Modulated Continuous-Wave (FMCW) principle. However, traditional FMCW radars face significant challenges in detecting low-speed motion due to the extremely small Doppler frequency shifts involved. This paper proposes an enhanced vehicle speed detection method using a multipulse FMCW radar system. The multipulse technique divides a single signal period into multiple short pulses, increasing spectral sampling density and improving Doppler resolution. MATLAB based simulation results demonstrate that the system can accurately detect speeds as low as 4 km/h by producing sharper and more distinguishable Doppler spectral peaks. The proposed approach shows strong potential for real-time traffic monitoring and intelligent transportation systems.